Normal Impact of A Rigid Cone-shaped against A Viscoelastic Plate on Viscoelastic Foundation - Manh, Duong Tuan (VNU Journal of Science: Mathematics - Physics, 2021)
This paper considers the problem of a low-velocity normal impact of a rigid cone-shaped upon a viscoelastic plate. The contact force is defined by the modified Hertz's contact law. Approximate solutions of the system of nonlinear integro-differential equations for the contact force and local indentation have been obtained.